21st century regionalism: Filling the gap between 21st century trade and 20th century trade rules - Richard Baldwin (World Trade Organization (WTO), 2011)
This paper weaves several sets of facts into an argument that: 1) today's trade is radically more complex, involving a trade-investment-service nexus, 2) this 21st century trade demanded deeper disciplines which were supplied by 21st century regionalism while the WTO was otherwise occupied, and 3) 21st century regionalism has quite different implications for the world trading system than the traditional thinking suggests. The paper also argues that the traditional thinking (building-stumbling-block and Vinerian economics) is not up to the job of analysing 21st century regionalism. An alternative framework is not provided, but elements a new approach should encompass are discussed.
Keywords: F13; F15; 330; regionalism; multilateralism; WTO; Handelsregionalismus; WTO-Regeln